The Impact of Digital Transformation Projects in Improving the Digital Confidence Scorecard by Applying to the Egyptian Ministry of Education and Technical Education - Kandel, Reda (The Arab Journal of Administration, 2025)
The study aimed to reveal the impact of the application of digital transformation projects on the dimensions of digital trust, as the study used the descriptive analytical approach, and relied on a questionnaire to collect statistical data from the study sample members, and included (41) paragraphs distributed over five dimensions (the first dimension to measure transformation projects). digital, and four dimensions of digital trust: the digital environment, user experiences, user attitudes and feelings, and user participation). A random sample of (105) affiliated to the Egyptian Ministry of Education (30 working in public administration and decision support systems, 75 teachers and parents in Cairo governorate) was selected representing the study population. To achieve the objectives of the research, several questions and hypotheses were raised that were tested based on the statistical program (SPSS), and the statistical means represented in the arithmetic mean, standard deviation and Pearson correlation coefficient were used, in order to measure the nature of the relationship between the research variables, and the simple linear regression coefficient to measure the effect relationships. The results of the study showed that all dimensions included in this scale came to a high degree, where the relative weight of the dimension of using technology and social media reached 76%, and it came in the first place, while the dimension of attitudes and feelings of users got a relative weight of 73.8% in the second place, as happened After the users experience a relative weight of 71.3%, it came in third place, and after the digital environment came in fourth place with a rate of 69.6%. In addition to the existence of a correlation and a significant effect between digital transformation and digital trust in its four dimensions, for the Ministry of Education, and this indicates that digital transformation projects have an important and effective role in improving the dimensions of digital trust.